Usage of Dermal Regeneration Templates (Pelnac) for Coverage of Exposed Hand Tendons in Acute Setting - Rama Ahmed Ali, MD; Ahmed Gamal Hemidan, MSc; Hamed Mohamed Kadry, MD; Ahmed Samy Saad, MD (Plastic and Reconstructive Surgery, Global Open, 2024)
Background:. The loss of soft tissue coverage of tendons is a challenging reconstructive problem after acute hand trauma. Subsequent tendon adhesions and the loss of range of movement in addition to the poor aesthetic outcome and donor site scarring should be avoided when deciding the plan of management. Pelnac is one of the commonly used skin substitutes in reconstructive surgery that can be used for coverage of exposed tendons, but the postoperative functional outcome needs to be addressed in detail. Methods:. Twenty-six patients with acute isolated tendon injuries distal to the wrist joint were included. Two-stage reconstructive procedures were performed; the first one was the application of Pelnac. The second stage was carried out after the complete integration of Pelnac via the application of a split-thickness graft. The function outcome assesses the return of the normal range of motion to the affected hand and the QuickDASH score questionnaire. The aesthetic outcome was assessed using the Vancouver scar scale. Results:. The Pelnac was integrated in 100% of cases, with complete grafts taken in 22 of 26 patients. The mean QuickDASH score was 20.5 ± 15.7, and mean Vancouver scar scale was 3.53 ± 3.2. The full range of motion returned in 22 of 26 patients. Conclusions:. Using Pelnac to cover the exposed hand tendons in an acute setting is a convenient and efficient procedure with minimal morbidity. It can offer a good option for their coverage with preservation of hand function and acceptable aesthetic outcome.